Leucine-enriched amino acid supplementation and exercise to prevent sarcopenia in patients on hemodialysis: a single-arm pilot study - Ju, Sang-Hyeon; Lee, Eu Jin; Sim, Byeong Chang; Nga, Ha Thi; Lee, Ho Yeop; Tian, Jingwen; Cho, Kyu Jeong; Park, Hyoungsu; Choi, Dae Eun; Ham, Young Rok; Yi, Hyon-Seung (Frontiers in Nutrition, 2023)
1.1 Background Sarcopenia, which is strongly associated with mortality and quality of life, occurs in up to 63% of hemodialysis patients. Here, we investigated the preventive effects of leucine-enriched amino acid supplementation and resistance exercise in non-sarcopenic hemodialysis patients, and characterized the biochemical and immunophenotypic profiles of those who benefited from the intervention. 1.2 Methods Twenty-two patients on maintenance hemodialysis at Chungnam National University Hospital were enrolled in this prospective single-arm interventional pilot trial. For the first 12 weeks, patients took a leucine-enriched amino acid supplement thrice daily and followed a daily exercise program. The intervention was then stopped for the next 12 weeks. Muscle mass, strength, physical performance, serum biochemistry, and the immunophenotype of peripheral blood mononuclear cells were evaluated at the baseline, 12-week, and 24-week time points (ClinicalTrials.gov identification number: NCT number). 1.3 Results The mean age and hemodialysis duration of participants were 55.3 years and 4.7 years, respectively. After 12 weeks of intervention, the skeletal muscle index increased in 63.6% and HGS improved in 31.8% of participants. The SPPB revealed that 59.1% and 63.6% of subjects showed more than 5% improvement in gait speed and in the five times sit-to-stand test (5TSTS), respectively, compared with baseline. Multivariate regression analyses revealed that HGS responders had a lower baseline HGS, that 5TSTS responders had lower baseline hematocrit, and that exercise compliance was an important predictor of HGS improvement. The cut-off value for an HGS response was a baseline HGS of 35.0 kg, and the cut-off value for a 5TSTS response was a baseline hematocrit level of 30.8% and a hemoglobin level of 10.5 g/dL. Immunophenotypic analysis found that the intervention tended to increase the naïve/memory CD8+ T cell ratio. Baseline CD3+CD56+ NK T cell counts in 5TSTS responders were higher than those in non-responders. 1.4 Conclusion A subpopulation of the cohort showed improvements in muscle mass, strength, and physical performance, as well as changes in serum biochemical and immunophenotypic characteristics. We propose that the intervention will help to prevent sarcopenia in patients on maintenance hemodialysis.